Sex-Related Differences in Atrial Remodeling in Patients With Atrial Fibrillation: Relationship to Ablation Outcomes. (January 2022) - Wong, Geoffrey R.; Nalliah, Chrishan J.; Lee, Geoffrey; Voskoboinik, Aleksandr; Chieng, David; Prabhu, Sandeep; Parameswaran, Ramanathan; Sugumar, Hariharan; Al-Kaisey, Ahmed; McLellan, Alex; Ling, Liang-Han; Sanders, Prashanthan; et al.
Abstract : Background: Population studies have demonstrated a range of sex differences including a higher prevalence of atrial fibrillation (AF) in men and a higher risk of AF recurrence in women. However, the underlying reasons for this higher recurrence are unknown. This study evaluated whether sex-based electrophysiological substrate differences exist to account for worse AF ablation outcomes in women. Methods: High-density electroanatomic mapping of the left atrium was performed in 116 consecutive patients with AF. Regional analysis was performed across 6 left atrium segments. High-density maps were created using a multipolar catheter (Biosense Webster) during distal coronary sinus pacing at 600 and 300 ms. Mean voltage and conduction velocity was determined. Complex fractionated signals and double potentials were manually annotated. Results: Overall, 42 (36%) were female, mean age was 61±8 years and AF was persistent in 52%. Global mean voltage was significantly lower in females compared with males at 600 ms (1.46±0.17 versus 1.84±0.15 mV, P <0.001) and 300 ms (1.27±0.18 versus 1.57±0.18 mV, P =0.013) pacing. These differences were seen uniformly across the left atrium. Females demonstrated significant conduction velocity slowing (34.9±6.1 versus 44.1±6.9 cm/s, P =0.002) and greater proportion of complex fractionated signals (9.9±1.7% versus 6.0±1.7%, P =0.014). After a median follow-up of 22 months (Q1–Q3: 15–29), females had significantly lower single-procedure (22 [54%] versus 54 [75%], P =0.029) and multiprocedure (24 [59%] versus 60 [83%], P =0.005) arrhythmia-free survival. Female sex and persistent AF were independent predictors of single and multiprocedure arrhythmia recurrence. Conclusions: Female patients demonstrated more advanced atrial remodeling on high-density electroanatomic mapping and greater post-AF ablation arrhythmia recurrence compared with males. These changes may contribute to sex-based differences in the clinical course of females with AF and in part explain the higher risk of recurrence. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.